Konsep Humas, Manajemen Humas, Fungsi Manajemen Humas, dan Kepemimpinan Humas di Lembaga Pendidikan - Shufiatuddin, Shabrina Ratu Alam; Tazkiyah, Ianatut (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This article based on previous research on the concept of public relations, public relations management, public relations management functions, and public relations leadership in educational institutions which identified that educational institutions needed efforts to combine social interests with promotion and marketing approaches. Combining these two interests is what makes educational institutions their own characteristics. Because of that, techniques and ways to manage information that are professional, efficient and effective to the public are needed. The approach used is a qualitative approach and the form of research is library research. Data collection techniques using documentation that traces from various kinds of literature and data analysis using critical analysis of research documents. The results shown in this study are an increase in student learning outcomes by applying various public relations concepts, management, functions, and leadership in educational institutions